Optimasi Perendaman Benih Kakao Menggunakan Asam Salisilat Mikroenkapsulasi: Dampak pada Vigor & Ekspresi Gen α-Amilase - Utama, Rayyan Febrian; Prananta, Surya (Lembaga Publikasi Ilmiah Nusantara, 2025)
Cacao (Theobroma cacao L.) is one of Indonesia’s strategic plantation commodities, with its economic value largely determined by seed quality. However, cacao germination is often hampered by low vigor and delayed enzymatic activity, particularly α-amylase, which plays a crucial role in starch mobilization. This study aimed to evaluate the effectiveness of cacao seed soaking using microencapsulated salicylic acid in improving seed vigor and the expression of the α-amylase gene. Cacao seeds were soaked in microencapsulated salicylic acid solution at various concentrations and compared with controls (non-soaked and soaked with non-encapsulated salicylic acid). Analyses included physiological parameters (germination percentage, vigor index, hypocotyl and radicle length) as well as molecular parameters (α-amylase gene expression measured by qRT-PCR). The results showed that soaking treatment with microencapsulated salicylic acid significantly improved seed vigor compared to controls. Moreover, α-amylase gene expression was higher in the microencapsulation treatment compared to the non-encapsulation treatment. These findings indicate that microencapsulation technology of salicylic acid has the potential to be developed as an innovative strategy to enhance the physiological quality of cacao seeds while strengthening the understanding of molecular mechanisms during germination.